PELATIHAN PENGUATAN MAHARAH KALAM BAGI SANTRI PONDOK PESANTREN DARUT TARBIYAH MANDAILING NATAL - Fadlan Masykura Setiadi; Zulpina Zulpina (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
This community service aimed to improve the speaking skills (mahārah kalām) of the Darut Tarbiyah Islamic Boarding School students using the Participatory Action Research approach. The results of community service showed that to improve students' speaking skills (mahārah kalām) it is necessary to apply relevant learning methods according to the characteristics of the students, among the methods carried out are as follows: 1) doing hiwār in pairs using sentence structures provided with intonation good and correct, 2) doing hiwār according to the context of the theme of the conversation precisely and smoothly, 3) imitating examples of uslub questions with good and correct intonation, 4) imitating examples of uslub answering questions with good and correct intonation, 5) getting used to doing hiwār according to the theme chosen by yourself with good and correct intonation